PENGARUH KARAKTERISTIK PEKERJAAN DAN LINGKUNGAN KERJA FISIK TERHADAP KOMITMEN ORGANISASI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PEGAWAI KANTOR GUBERNUR PROVINSI NTB) - Syahdan, Ratmaje (Jurnal Magister Manajemen, 2016)
This study aims to determine the effect of Job Characteristics and Physical Work Environment on Organizational Commitment with work motivation as an intervening variable in the employee of the Gubernur Province NTB. The population in this study are civil servants, amounting to 500 employees with a sampling technique that Proportionate Random Sampling totaled 83 civil servants. This type of research is associative causal research. Data collection tool was a questionnaire containing questions about the variables Job Characteristics, Work Environment Physical, Organizational Commitment and work motivation. Data analysis was performed with Path Analysis Model Triming using SPSS. The analysis finds that the job characteristics and significant positive effect on organizational commitment. Job characteristics and significant positive effect on work motivation. Physical work environment positive and significant effect on organizational commitment. Physical work environment positive and significant effect on work motivation. Work motivation positive and significant effect on organizational commitment. Job characteristics and significant positive effect on organizational commitment through work motivation. Physical work environment positive and significant effect on organizational commitment through motivation of employees working in the Office of Gubernur Province NTB. Keywords: Characteristic Employment, Physical Work Environment, Work Motivation and Organizational Commitment.